A role for platelets in metabolic reprogramming of tumor-associated macrophages - Kang, Ying; Amoafo, Emmanuel Boadi; Entsie, Philomena; Beatty, Gregory L.; Liverani, Elisabetta (Frontiers in Physiology, 2023)
Cancer incidence and mortality are growing worldwide. With a lack of optimal treatments across many cancer types, there is an unmet need for the development of novel treatment strategies for cancer. One approach is to leverage the immune system for its ability to survey for cancer cells. However, cancer cells evolve to evade immune surveillance by establishing a tumor microenvironment (TME) that is marked by remarkable immune suppression. Macrophages are a predominant immune cell within the TME and have a major role in regulating tumor growth. In the TME, macrophages undergo metabolic reprogramming and differentiate into tumor-associated macrophages (TAM), which typically assume an immunosuppressive phenotype supportive of tumor growth. However, the plasticity of macrophage biology offers the possibility that macrophages may be promising therapeutic targets. Among the many determinants in the TME that may shape TAM biology, platelets can also contribute to cancer growth and to maintaining immune suppression. Platelets communicate with immune cells including macrophages through the secretion of immune mediators and cell-cell interaction. In other diseases, altering platelet secretion and cell-cell communication has been shown to reprogram macrophages and ameliorate inflammation. Thus, intervening on platelet-macrophage biology may be a novel therapeutic strategy for cancer. This review discusses our current understanding of the interaction between platelets and macrophages in the TME and details possible strategies for reprogramming macrophages into an anti-tumor phenotype for suppressing tumor growth.